Effectiveness of Nursing Interventions on Preventing the Risk of Infection in Adult Inpatients: Protocol for a Systematic Review. - Todo Bom, Luís Filipe Pereira; Mata, Ema Soraia Fazenda; Cunha, Helena Margarida Pereira; Marquês, Maria do Céu Mendes Pinto; Dixe, Maria dos Anjos (Nursing Reports, 2025)
Background/Objectives: Healthcare-associated infections (HAIs) are a major global public health concern, significantly impacting patient safety and healthcare quality. These infections are associated with high morbidity and mortality rates, prolonged hospital stays, and increased healthcare costs. Nurses play a critical role in infection prevention, implementing evidence-based interventions to reduce infection risks. This systematic review aims to identify and synthesize the most effective nursing interventions to prevent HAIs in hospitalized adults, analyzing their variability across different clinical settings and populations. Methods: This systematic review follows the Joanna Briggs Institute (JBI) methodology for systematic reviews of effectiveness and is reported according to PRISMA guidelines. The protocol is registered in the PROSPERO database (CRD42024582820). This review includes randomized controlled trials, quasi-experimental studies, and observational studies (cohort, case-control, and cross-sectional) assessing the effectiveness of nursing interventions in reducing HAIs. A comprehensive search is conducted in the PubMed, CINAHL, Scopus, Web of Science, and Cochrane databases. Study selection, data extraction, and quality assessment are performed by two independent reviewers, with disagreements resolved by a third reviewer. Results: The primary outcomes include reductions in HAI incidence rate, increased adherence to preventive interventions, decreased hospital length of stay, reduced readmission rates due to infections, and overall patient safety improvements. A meta-analysis is conducted when feasible; otherwise, results are synthesized narratively. Conclusions: The findings of this review contribute to the standardization of evidence-based nursing practices for HAI prevention, promoting safer healthcare environments. By identifying the most effective interventions, this study aims to support healthcare professionals and policymakers in implementing targeted infection control strategies.